1997
DOI: 10.1038/bjc.1997.302
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin A is associated with an unfavourable outcome in patients with non-small-cell lung carcinomas

Abstract: Summary Specimens of formalin-fixed, paraffin-embedded non-small-cell lung carcinomas (NSCLCs; n = 187) were analysed immunohistochemically for expression of cyclin A. The analysis was intended to determine whether cyclin A has additional prognostic value for predicting patients' survival and drug response. Estimating the proliferative activity of tumours is important for the management and prognosis of tumour patients. Using flow cytometry in an earlier study, we found that patients with non-small-cell lung c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
68
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 7 publications
5
68
1
Order By: Relevance
“…We are aware of no clinical data on cyclin A as a predictive factor for chemotherapy in breast cancer. A preclinical study by Volm showed that breast cancer cell lines with high cyclin A were significantly more sensitive to doxorubicin than cell lines with low cyclin A activity (Volm et al, 1997). TFR: time to first relapse, TTPa: time to progression after anthracycline therapy, OSa: overall survival after anthracycline therapy, TTPdoc: time to progression after docetaxel therapy, OSdg: overall survival from diagnosis, OSdoc: overall survival after docetaxel therapy, MF: methotrexate fluorouracil, TTPmf: time to progression after methotrexate fluorouracil therapy, OSmf: overall survival after methotrexate fluorouracil therapy.…”
Section: Discussionmentioning
confidence: 99%
“…We are aware of no clinical data on cyclin A as a predictive factor for chemotherapy in breast cancer. A preclinical study by Volm showed that breast cancer cell lines with high cyclin A were significantly more sensitive to doxorubicin than cell lines with low cyclin A activity (Volm et al, 1997). TFR: time to first relapse, TTPa: time to progression after anthracycline therapy, OSa: overall survival after anthracycline therapy, TTPdoc: time to progression after docetaxel therapy, OSdg: overall survival from diagnosis, OSdoc: overall survival after docetaxel therapy, MF: methotrexate fluorouracil, TTPmf: time to progression after methotrexate fluorouracil therapy, OSmf: overall survival after methotrexate fluorouracil therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Kawashima et al reported that cytotoxicity of 5-FU in human cancer cell lines correlates with cyclin A. 39 In nonsmall-cell lung carcinomas, expression of cyclin A correlates with response of doxorubicin in vitro, 40 and patients with soft tissue sarcoma 41 or head and neck squamous cell carcinoma 42 expressing high levels of cyclin A show a better response to chemotherapy. These data suggest that cyclin A overexpression may prove useful in selecting those gastric cancer patients who may benefit from chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…There are very few reports on cyclin A as a marker of proliferative cell fraction in cancer. In two recent studies by Volm, tumour tissue negativity for cyclin A expression predicted a favourable outcome in non-small-cell lung cancer patients (Volm et al, 1997(Volm et al, , 1998. We are aware of no previous studies correlating cyclin A score of the tumour to chemotherapy response.…”
mentioning
confidence: 89%